2012
DOI: 10.3892/or.2012.1950
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-induced thermoablation with Amica-probe is a safe and reproducible method to treat solid renal masses: Results from a phase I study

Abstract: Abstract. Microwave thermal ablation (MWTA) could be considered in the future for treating small solid renal masses. The aim of the present study was to determine both the tolerability of the new Amica-probe applicator-induced MWTA used in vivo on patients with solid renal masses and the effects of heating on renal tumors and normal renal parenchyma. Fourteen patients with renal masses eligible for open radical nephrectomy were enrolled in this phase I study. All patients underwent MWTA of renal masses during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…It has been evaluated mainly in phase I studies with promising initial results. 64 A small phase II study showed complete tumour necrosis and no complications in 12 patients. 65…”
Section: Novel Treatment Modalitiesmentioning
confidence: 98%
“…It has been evaluated mainly in phase I studies with promising initial results. 64 A small phase II study showed complete tumour necrosis and no complications in 12 patients. 65…”
Section: Novel Treatment Modalitiesmentioning
confidence: 98%
“…It allows maximum control over radial and longitudinal ablative lesion size and overcomes back heating effects, while keeping the applicator size at a minimum. 21 …”
Section: Devices For Delivery Of Thermal Treatmentmentioning
confidence: 99%
“…Studies conducted in rabbits that previously had tumor implantation show that percutaneous microwave ablation can achieve results similar to those of open nephrectomy having thus the potential of being a nephron salvaging treatment for small renal tumors [23]. However, microwaves have some limitations in particular in relation to the design of the antenna that does not allow a complete control of the lesion during the ablation with an oval shape of coagulation [24,25].…”
Section: Experimental Comparison To Other Thermal Ablative Techniquesmentioning
confidence: 99%
“…Histochemical examinations revealed no cell death beyond the ablation area: this is particularly important in renal ablation to preserve healthy parenchyma and, above all, vascular and caliceal structures [28]. In the following year, Bartoletti et al [23] published another phase I study with the aim to determine the tolerability of the Amica-probe in vivo in patients with solid renal masses and the effects of heating on renal tumors and normal renal parenchyma. No local bleeding after treatment was reported showing the reduced risk of bleeding of MWA [23].…”
Section: Microwave Ablation In Kidney: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation